Model Pembelajaran VAK (Visual, Auditory, Kinestetic) Terhadap Hasil Belajar Bahasa Jepang pada Siswa Kelas XI IPA SMA Al Hasra, Depok - Camila Dwi Putri; Rina Sukmara; Retno Utari (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
The purpose of this study is to determine the effectiveness of the VAK (Visual, Auditory, Kinesthetic) Learning Model on Japanese Language Learning Outcomes for SMA Al Hasra Depok Class XI Science Students. The True Experiment Design method is used in this study. This study's population consists of 30 students from class XI IPA 3 and 30 students from class XI IPA 1. The experimental class received a score of 82.3 based on data calculations, while the control class received a score of 66.0. The independent sample t-test formula for the SPSS 24 program was used to test hypotheses, with a significance level of p-value 0.05. The result of the t test calculation is 0.000. The experimental class has a normalized gain of 39.57, while the control class has a gain of 8.74. The VAK (Visual, Auditory, Kinesthetic) learning model is said to be effective for improving learning outcomes in Japanese lessons based on this value. According to student feedback, the VAK (Visual, Auditory, Kinesthetic) learning model is enjoyable, motivates students to learn, and makes Japanese simple to understand.